2019
DOI: 10.1038/s41467-019-09959-4
|View full text |Cite|
|
Sign up to set email alerts
|

Discrepancy in scientific authority and media visibility of climate change scientists and contrarians

Abstract: We juxtapose 386 prominent contrarians with 386 expert scientists by tracking their digital footprints across ∼200,000 research publications and ∼100,000 English-language digital and print media articles on climate change. Projecting these individuals across the same backdrop facilitates quantifying disparities in media visibility and scientific authority, and identifying organization patterns within their association networks. Here we show via direct comparison that contrarians are featured in 49% more media … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 55 publications
0
43
0
4
Order By: Relevance
“…The disproportionate attention given to contrarians or the skeptical, leaves the audience susceptible to an increased confusion regarding climate change and thus the public's widespread environmental alienation. As such, it is argued that editors should adjust the disproportionate attention given to these figures and to conflicting debates [42]. Yet, regarding actors' discourses and similar to findings of previous studies [7], the discourse of general public/users is barely reported in the European media.…”
Section: Discussionmentioning
confidence: 52%
“…The disproportionate attention given to contrarians or the skeptical, leaves the audience susceptible to an increased confusion regarding climate change and thus the public's widespread environmental alienation. As such, it is argued that editors should adjust the disproportionate attention given to these figures and to conflicting debates [42]. Yet, regarding actors' discourses and similar to findings of previous studies [7], the discourse of general public/users is barely reported in the European media.…”
Section: Discussionmentioning
confidence: 52%
“…Repetition, not evidence, corroborates these estimates…" is ironic, given that his articles exhibit a clear pattern of self-citation and repetition of unsubstantiated arguments (Ricciardi & Ryan 2018b). In contrast to informed sceptics who advance science, denialists mislead scientists, stakeholders, and policy makers by repeating debunked claims (Petersen et al 2019). We urge journal editors to reconsider acceptance of denialist essays, despite potential boosts to impact factor.…”
Section: Resultsmentioning
confidence: 95%
“…In contrast to informed sceptics who advance science, denialists mislead scientists, stakeholders, and policy makers by repeating debunked claims (Petersen et al. 2019). We urge journal editors to reconsider acceptance of denialist essays, despite potential boosts to impact factor.…”
Section: Resultsmentioning
confidence: 99%
“…3 Meanwhile 'experts' are derided 4 and climate change deniers and other contrarians can reach huge audiences via online platforms. 5 In March 2017 Berners-Lee himself expressed concern about the web's future, highlighting how easily misinformation can spread, due in part to corporations harvesting and abusing personal data. 6 Disparate platforms with different agendas, in some cases outright disinformation, can result in users retreating into a 'filter bubble' of trusted friends and family on social media, thus making them vulnerable to algorithmically targeted messages with a political or commercial agenda.…”
Section: Tim Berners-leementioning
confidence: 99%